Moderasi Penafsiran Di Tengah Ragam Qira’at: Analisis Ayat Taharah Perspektif Imam Qurtubi - Fadli, Muhammad; Al Faruq, Abdul Qudus; Azizah, Wafik (Universitas Cokroaminoto Yogyakarta, 2025)
The emergence of new Islamic groups in Indonesia often sparks debates regarding the validity of qirāʾāt and the interpretation of the Qur’an, with each group claiming to hold the most authentic understanding. The diversity of qirāʾāt poses a challenge in maintaining unity among Muslims. Imam Qurṭūbī, through his moderate approach, emphasizes the importance of objectively understanding these variations without excessive bias. This study employs a descriptive analytical method with a qualitative approach based on library research. It focuses on the analysis of Ṭahārah verses in Surah Al-Ma’idah (5:6) and Surah An-Nisa (4:43). The findings indicate that Imam Qurṭūbī elaborates on qirāʾāt differences in detail without prioritizing one over another, reflecting a balanced interpretative approach. This moderation offers a solution for addressing differences while strengthening Muslim unity.